Pioneering Study on Rhopalurus crassicauda Scorpion Venom: Isolation and Characterization of the Major Toxin and Hyaluronidase - Abreu, Caio B.; Bordon, Karla C. F.; Cerni, Felipe A.; Oliveira, Isadora S.; Balenzuela, Carla; Alexandre-Silva, Gabriel M.; Zoccal, Karina F.; Reis, Mouzarllem B.; Wiezel, Gisele A.; Peigneur, Steve; Pinheiro-Júnior, Ernesto L.; Tytgat, Jan; et al. (Frontiers in Immunology, 2020)
Scorpionism is responsible for most accidents involving venomous animals in Brazil, which leads to severe symptoms that can evolve to death. Scorpion venoms consist of complexes cocktails, including peptides, proteins, and nonprotein compounds, making separation and purification procedures extremely difficult and time-consuming. Scorpion toxins target different biological systems and can be used in basic science, for clinical, and biotechnological applications. This study is the first to explore the venom content of the unexplored scorpion species Rhopalurus crassicauda, which inhabits exclusively the northernmost state of Brazil, named Roraima, and southern region of Guyana. Here, we pioneer the fractionation of the R. crassicauda venom and isolated and characterized a novel scorpion beta-neurotoxin, designated Rc1, and a monomeric hyaluronidase. R. crassicauda venom and Rc1 (6,882 Da) demonstrated pro-inflammatory activities in vitro and a nociceptive response in vivo. Moreover, Rc1 toxin showed specificity for activating Nav1.4, Nav1.6, and BgNav1 voltage-gated ion channels. This study also represents a new perspective for the treatment of envenomings in Roraima, since the Brazilian scorpion and arachnid antivenoms were not able to recognize R. crassicauda venom and its fractions (with exception of hyaluronidase). Our work provides useful insights for the first understanding of the painful sting and pro-inflammatory effects associated with R. crassicauda envenomings.